Preparation method of ruthenium trichloride

Through the calcination method combining porous manganese dioxide catalyst with CO2 atmosphere, the problems of low ruthenium recovery rate and incomplete carbon deposit removal in waste ruthenium alumina catalyst were solved, efficient ruthenium recovery and carbon deposit removal were achieved, and the recovery rate and economy of the catalyst were improved.

CN120717528AActive Publication Date: 2025-09-30SHANDONG CHENYOU ECOLOGICAL & ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511235762.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-09-30
Estimated Expiration
2045-09-01

AI Technical Summary

Technical Problem

Existing technologies make it difficult to efficiently recover and utilize ruthenium in spent ruthenium-alumina catalysts, and the loss of ruthenium is easily caused during the carbon deposit removal process.

Method used

A porous manganese dioxide catalyst is mixed with a waste ruthenium alumina catalyst, calcined in a CO2 atmosphere, and combined with hydrochloric acid leaching, alkali fusion, water leaching, acidification and oxidative distillation steps. Through the physical stripping and catalytic effect of the porous manganese dioxide catalyst, the carbon deposit removal efficiency is improved and the ruthenium loss is reduced.

Benefits of technology

Efficient recovery of ruthenium trichloride was achieved, with the ruthenium recovery rate and carbon deposit removal rate both reaching over 98.7%, reducing production costs and promoting the recycling of precious metal resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120717528A_ABST
    Figure CN120717528A_ABST
Patent Text Reader

Abstract

The invention provides a ruthenium trichloride preparation method, which comprises: (1) mixing a waste ruthenium-alumina catalyst and a porous manganese dioxide catalyst, the specific surface area of the porous manganese dioxide catalyst is not less than 80 m < 2 > / g, the average particle size is 1-5 [mu] m, and the mass ratio of the catalyst to the waste ruthenium-alumina catalyst is (1-5): 100; (2) putting the mixture into a vertical pyrolyzing furnace with a mechanical stirring device, and roasting for 2-3.5 hours at the temperature of 620-650 DEG C in a CO2 atmosphere at the stirring speed of 300-500 rpm; and (3) cooling after roasting is finished, and carrying out hydrochloric acid leaching, solid-liquid separation, alkali fusion, water leaching, acidification and oxidative distillation to obtain a ruthenium trichloride solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst recovery in the petroleum industry, and specifically to a method for preparing ruthenium trichloride. Background Art

[0002] With the development of the petrochemical industry, the consumption of ruthenium-based catalysts has increased annually, and the production of ruthenium-containing catalysts has also increased accordingly. Recovering ruthenium from spent ruthenium catalysts in the form of ruthenium chloride has great industrial application value. Ruthenium chloride is widely used in the basic chemical and pharmaceutical chemical industries. Furthermore, it can achieve efficient recycling of ruthenium from spent catalysts, which not only helps alleviate the shortage of precious metal resources but also reduces production costs for enterprises, with important economic and environmental significance. Summary of the Invention

[0003] In order to solve the above technical problems, the present application provides a method for preparing ruthenium trichloride, comprising the following steps: (1) mixing a waste ruthenium alumina catalyst with a porous manganese dioxide catalyst, wherein the specific surface area of ​​the porous manganese dioxide catalyst is not less than 80 m 2 / g, with an average particle size of 1-5 μm, and a mass ratio of the catalyst to the spent ruthenium alumina catalyst of (1-5):100; (2) placing the mixture in a vertical pyrolysis furnace equipped with a mechanical stirring device, and calcining it at 620-650°C for 2-3.5 hours in a CO2 atmosphere with a stirring speed of 300-500 rpm; (3) cooling after the calcination, and performing hydrochloric acid leaching, solid-liquid separation, alkali fusion, water leaching, acidification and oxidative distillation to obtain a ruthenium trichloride solution.

[0004] This method effectively improves the removal efficiency of carbon deposits in waste ruthenium alumina catalysts by combining a porous manganese dioxide catalyst with a carbon dioxide atmosphere, while reducing the loss of ruthenium. The particle size of the porous manganese dioxide is similar to the pore size of the catalyst. Under high-speed stirring, it can enter the internal channels of the catalyst, physically peel off and rub deep carbon deposits, and help desorb and decompose the carbon deposits. Manganese dioxide, as a catalyst, can promote the reaction between carbon dioxide and carbon deposits, so that the carbon deposits are converted into carbon monoxide gas at a lower temperature and discharged from the system. The carbon dioxide atmosphere not only provides reactants for carbon deposit removal, but also effectively inhibits the oxidation and volatilization of ruthenium elements, preventing the loss of ruthenium elements at high temperatures. High-speed stirring ensures the uniform distribution of the manganese dioxide catalyst between the catalyst particles, enhances the contact efficiency between the catalyst and carbon deposits, and also promotes the flow of gas in the bed and the uniformity of the reaction. After the roasting is completed, the manganese dioxide catalyst and the catalyst can be efficiently separated by solid-liquid separation, realizing the recovery and recycling of the catalyst and avoiding its impact on subsequent processes.

[0005] Furthermore, the porous manganese dioxide catalyst is prepared using a sol-gel method, which helps to obtain porous manganese dioxide with a uniform structure and a high specific surface area, thereby improving the catalytic activity and dispersibility of the catalyst.

[0006] Specifically, the specific surface area of ​​the porous manganese dioxide catalyst is 90-120 m 2 / g. This specific surface area further enhances the contact interface between the catalyst and carbon deposits, thereby improving the carbon deposit removal efficiency.

[0007] Furthermore, the solid-liquid separation uses a filter with a pore size of 10-50 μm. A suitable filter pore size helps to efficiently separate the porous manganese dioxide catalyst from the catalyst and improve the catalyst recovery rate.

[0008] Furthermore, the alkali fusion step includes mixing the catalyst after hydrochloric acid leaching with Na2O2 and NaOH, and alkali fusion at 600-700°C for 1.5-3 hours. This condition helps to completely decompose residual impurities and promote the conversion of ruthenium.

[0009] Specifically, the mass ratio of Na2O2 to NaOH is 1:0.75-1:1. A reasonable base ratio helps control the alkalinity and fluidity of the reaction system and improve the conversion efficiency of ruthenium.

[0010] Furthermore, the acidification step includes dropwise adding 40-98% sulfuric acid by mass to the water filtrate of the alkali fusion product and heating it to 90-100° C. This step helps to fully acidify the system and create favorable conditions for subsequent oxidative distillation.

[0011] Furthermore, the oxidative distillation step includes dropwise addition of NaClO₃ to the acidified solution to oxidize Ru to RuO₄, which is then absorbed with 30-37% hydrochloric acid to obtain a ruthenium trichloride solution. This step efficiently converts ruthenium into soluble ruthenium trichloride, facilitating subsequent purification and utilization.

[0012] Furthermore, the stirring speed in the calcination step is 350-450 rpm. A higher stirring speed is conducive to the thorough mixing of the catalyst and the catalyst particles and the efficient removal of carbon deposits.

[0013] Furthermore, the mass ratio of the porous manganese dioxide catalyst to the spent ruthenium alumina catalyst is 1:30 to 1:40. This ratio helps to reduce the amount of catalyst used while ensuring a synergistic catalytic effect, thereby improving economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The present invention is a flow chart of the method for preparing ruthenium trichloride. DETAILED DESCRIPTION

[0015] For ease of understanding of the present application, the present application will be described more fully below. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0016] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of such features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of this application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application pertains. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0018] In this application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0019] In this application, when referring to numerical ranges, unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges subsumed therein.

[0020] Unless otherwise specified, the percentage contents mentioned in this application refer to mass percentage for solid-liquid mixture and solid-solid mixture, and refer to volume percentage for liquid-liquid mixture.

[0021] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.

[0022] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows for temperature fluctuations within the precision range of instrument control.

[0023] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape but may be irregular, primary or secondary. The particle size of irregular particles is the average of their maximum and minimum diameters.

[0024] Example 1: This example provides a method for preparing ruthenium trichloride.

[0025] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 0.5 kg of porous manganese dioxide catalyst, average particle size 3 μm, specific surface area 90 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 3 μm and a specific surface area of ​​90 m 2 / g of porous manganese dioxide powder.

[0026] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring device was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 650°C and then calcined at this temperature for 3 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0027] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0028] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0029] Example 2: This example provides a method for preparing ruthenium trichloride.

[0030] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 0.5 kg of porous manganese dioxide catalyst, average particle size 1.5 μm, specific surface area 120 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 1.5 μm and a specific surface area of ​​120 m 2 / g of porous manganese dioxide powder.

[0031] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring device was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 650°C and then calcined at this temperature for 2.5 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0032] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0033] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0034] Example 3: This example provides a method for preparing ruthenium trichloride.

[0035] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 0.5 kg of porous manganese dioxide catalyst, average particle size 3 μm, specific surface area 90 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 3 μm and a specific surface area of ​​90 m 2 / g of porous manganese dioxide powder.

[0036] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring device was activated and set to 500 rpm. The temperature was increased at a rate of 10°C / min to 620°C and then calcined at a constant temperature for 3 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0037] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0038] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0039] Example 4: This example provides a method for preparing ruthenium trichloride.

[0040] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 1 kg of porous manganese dioxide catalyst, average particle size 3 μm, specific surface area 90 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 3 μm and a specific surface area of ​​90 m 2 / g of porous manganese dioxide powder.

[0041] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring device was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 650°C and then calcined at this temperature for 2 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0042] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0043] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0044] Example 5: This example provides a method for preparing ruthenium trichloride.

[0045] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 0.5 kg of porous manganese dioxide catalyst, average particle size 3 μm, specific surface area 90 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 3 μm and a specific surface area of ​​90 m 2 / g of porous manganese dioxide powder.

[0046] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring device was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 650°C and then calcined at this temperature for 3 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0047] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0048] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (1:1 mass ratio) and placed in an electric furnace for alkali fusion at 700°C for 2 hours. The alkali fusion product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by adding 98% sulfuric acid dropwise. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0049] Example 6: This example provides a method for preparing ruthenium trichloride.

[0050] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 0.5 kg of porous manganese dioxide catalyst, average particle size 5 μm, specific surface area 80 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 5 μm and a specific surface area of ​​80 m 2 / g of porous manganese dioxide powder.

[0051] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was pre-circulated into the furnace for 30 minutes to displace the air. The stirring mechanism was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 650°C and then calcined at this temperature for 3.5 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0052] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0053] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0054] Example 7: This example provides a method for preparing ruthenium trichloride.

[0055] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 0.2 kg of porous manganese dioxide catalyst, average particle size 1 μm, specific surface area 140 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 1 μm and a specific surface area of ​​140 m 2 / g of porous manganese dioxide powder.

[0056] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was pre-circulated into the furnace for 30 minutes to displace the air. The stirring mechanism was activated and set to 300 rpm. The temperature was increased at a rate of 10°C / min to 620°C and then calcined at a constant temperature for 3 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0057] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 10 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0058] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0059] Example 8: This example provides a method for preparing ruthenium trichloride.

[0060] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles, containing approximately 0.5 wt% ruthenium and 8 wt% carbon), particle size 2-10 mm, dried to constant weight. 0.67 kg of porous manganese dioxide catalyst, average particle size 3 μm, specific surface area 90 m 2 / g, was prepared by the sol-gel method, specifically: potassium permanganate was dissolved in deionized water, sodium citrate was added as a complexing agent, the pH was adjusted to 7-8, and the mixture was stirred in a water bath at 60°C for 2 hours. The obtained sol was dried at 120°C for 12 hours, and the dried product was calcined in air at 400°C for 4 hours, and then ground through a 100-mesh sieve to obtain an average particle size of 3 μm and a specific surface area of ​​90 m 2 / g of porous manganese dioxide powder.

[0061] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring mechanism was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 700°C and then calcined at this temperature for 1.5 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0062] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 50 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0063] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 40% sulfuric acid. The temperature was raised to 90°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 30% hydrochloric acid to obtain a ruthenium trichloride solution.

[0064] Comparative Example 1: This comparative example provides a method for preparing ruthenium trichloride.

[0065] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical enterprise's hydrogenation unit, gray-black cylindrical particles, containing about 0.5wt% ruthenium and about 8wt% carbon), with a particle size of 2-10 mm, dried to constant weight.

[0066] The catalyst was transferred to a vertical pyrolysis furnace. Air (3000 L / h) was pre-circulated through the furnace for 30 minutes. The stirring mechanism was activated and set to 400 rpm. The temperature was raised at a rate of 10°C / min to 650°C and then calcined at this temperature for 3 hours. Air was continuously introduced throughout the furnace, maintaining a positive pressure of 0.02 MPa.

[0067] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and ventilation were continued until the temperature dropped below 100°C. After calcination, the mixture was cooled and transferred to a 500 L polypropylene stirring tank. 60 L of 30% hydrochloric acid was added for leaching. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the catalyst particles (filter residue).

[0068] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0069] Comparative Example 2: This comparative example provides a method for preparing ruthenium trichloride.

[0070] 20 kg of petrochemical waste ruthenium alumina catalyst (from a petrochemical enterprise's hydrogenation unit, gray-black cylindrical particles, containing about 0.5wt% ruthenium and about 8wt% carbon), with a particle size of 2-10 mm, dried to constant weight.

[0071] The catalyst was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring device was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 650°C and then calcined at this temperature for 3 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0072] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation were continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the catalyst particles (filter residue).

[0073] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0074] Comparative Example 3: This comparative example provides a method for preparing ruthenium trichloride.

[0075] 20 kg of petrochemical waste ruthenium-alumina catalyst (from a petrochemical company's hydrogenation unit, gray-black cylindrical particles with approximately 0.5 wt% ruthenium and 8 wt% carbon content), particle size 2-10 mm, dried to constant weight. 0.5 kg of commercially available porous manganese dioxide catalyst, average particle size 50 μm.

[0076] The mixture was transferred to a vertical pyrolysis furnace. CO₂ gas (99.99% purity, 3000 L / h) was introduced into the furnace for 30 minutes to displace the air. The stirring device was activated and set to 400 rpm. The temperature was increased at a rate of 10°C / min to 650°C and then calcined at this temperature for 3 hours. During this time, CO₂ gas was continuously introduced to maintain a positive pressure in the furnace (0.02 MPa).

[0077] After calcination, heating was stopped and the mixture was allowed to cool naturally to room temperature. Stirring and CO2 ventilation continued until the temperature dropped below 100°C. After calcination and cooling, the cooled calcined product was transferred to a 500 L polypropylene stirring tank and leached with 60 L of 30% hydrochloric acid. The mixture was stirred at 95°C for 2 hours, filtered, and then 300 L of deionized water was added. The mixture was stirred at high speed for 20 minutes, ultrasonically treated for 10 minutes (power 1 kW, frequency 40 kHz), and filtered (filter mesh pore size 20 μm) to separate the porous manganese dioxide catalyst (in the liquid phase) and the catalyst particles (filter residue).

[0078] The filter residue was mixed with 20 kg of Na₂O₂ and NaOH (mass ratio 1:0.75) and subjected to alkaline fusion in an electric furnace at 650°C for 2.5 hours. The alkali-fused product was added to 100 L of deionized water and stirred at 95°C for 3 hours. The mixture was filtered and the filtrate was collected. The filtrate was acidified to pH 1 by dropwise addition of 98% sulfuric acid. The temperature was raised to 95°C, and 10 wt% NaClO₃ was added dropwise until the solution turned yellow. Stirring was continued for 30 minutes. The generated RuO₄ gas was absorbed with 36% hydrochloric acid to obtain a ruthenium trichloride solution.

[0079] The ruthenium recovery rate and carbon deposit removal rate of the above process were tested.

[0080] Ruthenium recovery rate: The ruthenium content in the product ruthenium trichloride solution was measured by ICP-OES and compared with the original ruthenium content in the catalyst to calculate the recovery rate.

[0081] Carbon deposit removal rate: The catalyst particles were sampled before and after calcination, and the carbon content was determined by TGA thermogravimetric analysis to calculate the removal rate.

[0082] The test data of the embodiments and comparative examples are shown in the following table.

[0083] Table 1 Ruthenium recovery rate and carbon deposit removal rate of Examples and Comparative Examples.

[0084] serial number Calcination time (h) Ruthenium recovery rate (%) Carbon deposit removal rate (%) Example 1 3 99.3 97.8 Example 2 2.5 99.5 98.6 Example 3 3 99.1 97.2 Example 4 2 99.6 99.0 Example 5 3 99.2 97.5 Example 6 3.5 98.7 95.8 Example 7 3 98.8 96.8 Example 8 1.5 99.1 97.6 Comparative Example 1 3 93.8 98.5 Comparative Example 2 3 85.2 38.2 Comparative Example 3 3 90.0 83.2 As can be seen from Table 1, all examples achieved high ruthenium recovery rates (above 98.7%) and carbon deposit removal rates (above 95.8%), with short roasting times and high additive recovery rates, demonstrating the high efficiency and green recycling characteristics of this process. In comparison, Comparative Example 1 uses an air atmosphere, so its carbon deposit removal rate is higher, but there is a situation where some ruthenium is oxidized to form ruthenium dioxide and then volatilized and lost, resulting in a lower ruthenium recovery rate; Comparative Example 2 uses a carbon dioxide atmosphere, but no manganese dioxide is added, the reaction efficiency of carbon deposits and carbon dioxide is too low, and the carbon deposit removal rate is too low, which will make it difficult to fully release ruthenium during the subsequent acid leaching and alkali fusion processes; Comparative Example 3 uses conventional manganese dioxide. Although its ruthenium recovery rate and carbon deposit removal rate are improved compared with Comparative Example 2, because its particle size is too large, much larger than the size of the catalyst pores, it is difficult to enter the interior of the catalyst, and it is impossible to effectively strip and catalyze to remove deep carbon deposits. Part of the ruthenium is still coated inside the carbon deposit, and it is difficult to fully dissolve ruthenium in the subsequent acid leaching and alkali fusion steps, resulting in a ruthenium recovery rate that is lower than that of Example 1, and is also lower than that of Comparative Example 1 calcined under an air atmosphere.

[0085] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0086] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.

Claims

1. A method for preparing ruthenium trichloride, characterized in that: The following steps are involved: (1) Mixing the spent ruthenium alumina catalyst with a porous manganese dioxide catalyst, wherein the specific surface area of ​​the porous manganese dioxide catalyst is not less than 80 m 2 / g, the average particle size is 1-5 μm, and the mass ratio of catalyst to spent ruthenium alumina catalyst is (1-5):100; (2) placing the mixture in a vertical pyrolysis furnace equipped with a mechanical stirring device, and calcining it at 620-650°C for 2-3.5 hours under a CO2 atmosphere with a stirring speed of 300-500 rpm; (3) After roasting, the mixture is cooled, subjected to hydrochloric acid leaching, solid-liquid separation, alkali fusion, water leaching, acidification and oxidative distillation to obtain a ruthenium trichloride solution.

2. The preparation method according to claim 1, characterized in that The porous manganese dioxide catalyst is prepared by a sol-gel method.

3. The preparation method according to claim 1, characterized in that The specific surface area of ​​the porous manganese dioxide catalyst is 90-120 m² / g.

4. The preparation method according to claim 1, characterized in that The solid-liquid separation uses a filter with a pore size of 10-50 μm.

5. The preparation method according to claim 1, characterized in that The alkali melting step comprises mixing the catalyst leached with hydrochloric acid with Na2O2 and NaOH, and alkali melting the mixture at 600-700°C for 1.5-3 hours.

6. The preparation method according to claim 5, characterized in that The mass ratio of Na2O2 to NaOH is 1:0.75-1:

1.

7. The preparation method according to claim 1, characterized in that The acidification step comprises dropwise adding sulfuric acid with a mass fraction of 40-98% into the water leaching filtrate of the alkali fusion product and heating the solution to 90-100°C.

8. The preparation method according to claim 1, characterized in that The oxidation distillation step includes dropwise adding NaClO3 into the acidified solution to oxidize Ru to RuO4, and absorbing it with hydrochloric acid with a mass fraction of 30-37% to obtain a ruthenium trichloride solution.

9. The preparation method according to claim 1, characterized in that The stirring speed in the roasting step is 350-450 rpm.

10. The preparation method according to claim 1, characterized in that The mass ratio of the porous manganese dioxide catalyst to the spent ruthenium alumina catalyst is 1:30 to 1:40.

Citation Information

Patent Citations

  • Catalysts based on natural minerals and process for gasification using the same

    CN105312056A

  • Method of recycling ruthenium trichloride from waste carbon ruthenium-supporting catalyst

    CN106186090A

  • Method for recovering noble metal from waste alumina carrier noble metal catalyst

    CN112981105A

  • Method for recovering ruthenium from ruthenium-containing catalyst

    CN117904443A

  • Recovery method of alumina carrier platinum group metal-containing catalyst

    CN118880036A